If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w = -5w + -36 Reorder the terms: 4w = -36 + -5w Solving 4w = -36 + -5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '5w' to each side of the equation. 4w + 5w = -36 + -5w + 5w Combine like terms: 4w + 5w = 9w 9w = -36 + -5w + 5w Combine like terms: -5w + 5w = 0 9w = -36 + 0 9w = -36 Divide each side by '9'. w = -4 Simplifying w = -4
| 25m^2+35m+10=0 | | -7t=-5t+2 | | 24x-3=-16x+27 | | 113-(5x+6)=5(x+6)+x | | 2w+12=7w-3 | | 2(2m-5)=4m+7 | | (-7+i)(9+i)= | | 43-(5x+60)=5(x+3)+x | | (x^2)-(2*x)+0.4=0 | | -8v-18=-2(4v+9) | | 3i-(16-4i)= | | x(55)+x(285)=1020 | | 2q+4=8 | | (7+4i)-(9-5i)= | | 5y-30=50 | | 25y-30=50-20y | | 5y^2+24y-5=0 | | f^2-6f+5=0 | | (7-4i)+(9+6i)= | | -6+5a=16+6a | | .25(x-1)+x=1 | | -4y=6y-8 | | 4a-2b-72=0 | | f(x)=-x^2+300x+6 | | 9z-6=9z-6 | | (3x^2)(-5y^3)(-6z)=a | | 5y-(2y+8)=16 | | 40k-24=60k+12 | | [5(x+7)-11]-[3(x-9)+12]= | | 11u^2-13u+2=0 | | 4b+4=4b-1 | | 4f^2+12f+9=0 |